Beneficial Action of 2,4,4-Trimethyl-3-(15-hydroxypentadecyl)-2-cyclohexen-1-one, a Novel Long-Chain Fatty Alcohol, on Diabetic Hypoalgesia and Neuropathic Hyperalgesia - Yutaka Tamura; Mayuko Monden; Hiroto Suzuki; Masashi Yamada; Keizo Koyama; Hirohito Shiomi (Elsevier, 2006)
The effects of 2,4,4-trimethyl-3-(15-hydroxypentadecyl)-2-cyclohexen-1-one (tCFA15) on diabetic hypoalgesia and neuropathic hyperalgesia were examined. Treatments of streptozotocin (STZ)-pretreated mice with tCFA15 (8 - 40 mg/kg, i.p.) for 7 days significantly reversed the depressed inflammatory nociceptive licking response in the formalin test. In addition, similar drug treatments and dosing in 7-day postoperative neuropathic pain model rats (prepared by the method of Bennett and Xie) yielded a similarly favorable outcome by significantly reversing decreased nociceptive thresholds in the paw pressure test. These results suggest that tCFA15 may have the potential to normalize sensory nerve abnormalities induced in experimental diabetes and nerve injury. Keywords:: diabetic hypoalgesia, long-chain fatty alcohol, chronic constriction injury